Planning for success (endurance training program design) - Schmidt, A.; Christensen, S. (Techniques Magazine, 2024)
In this chapter taken from the Endurance Specialist Certification course curriculum, the general concepts that guide the designing of an endurance training program are outlined. Topics include periodization of training and the terms used to describe the various components of training.